Evalution of Anti-Arthritic Potential of Siddha Formulation ChanthirothayaMathirai on Freund‘s Adjuvant-Induced arthritis in Wistar rats - Devi, P. V. Sudhaa (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: Rheumatoid arthritis (RA) is an autoimmune, chronic multisystem disease with various systemic manifestations resulting in joint damage and physical disability. The Siddha system of medicine is one of the traditional system of Indian medicine, which comprises ennumber of siddha formulations for RA. The tablet ChanthirothayaMathirai (CHTM), a herbomineral siddha formulation is found to be efficacious for RA. The present study focuses on theevaluation of anti-arthritic potential of Siddha formulation CHTM on complete Freund’s adjuvant (CFA)-induced arthritis model. Materials and Methods: The animals were grouped into three. Group I received normal saline, Group II received 0.1 ml of CFA in the left hind and treated with 250 mg/kg of CHTM from day 1 to 21, and Group III received 0.1 ml of CFA into the left hind and treated with 500 mg/kg of CHTM from day 1 to 21. The biochemical parameters were carried out on all groups after 21 days. The presence of any adverse effects was also recorded throughout the study. Results: A significant increase in the paw volume and thickness of CFA-injected paws compared to the normal control paws was observed. Arthritic assessment scoring revealed that CFA-injected paws were with the maximum scoring of 3.8. The treatment with CHTM at both doses has significantly decreased arthritic scoring to 2.3. Results showed marginal signs of rejuvenation with mild cartilages destruction with restoring histology of synovium and bone morphology were observed in low-dose drug-treated rats. High-dose drug-treated rats showed normal histomorphology of synovium. Conclusion: The study concluded that the trial drug CHTM at the dose of 250 and 500 mg/kg showed a significant reduction in joint swelling with a reversal in bone and tissue morphology. Thus, CHTM formulation offers a strong protective effect against Freund’s complete adjuvant-induced paw edema in rats. Hence, the drug CHTM has been scientifically validated for its anti-arthritic potential in management of RA.